Global trends in Alzheimer’s disease and other dementias: A comprehensive analysis of incidence, socio-demographic variations, and future projections - Ruixue Qin; Huijuan Zhao; Hui Gao; He Liu (PLoS ONE, 2025)
Background Alzheimer’s disease and other dementias (ADRD) are significant global health concerns, with rising incidence rates and substantial social and economic implications due to population aging. Methods We investigated trends in ADRD incidence from 1992 to 2021 across age, sex, and socio-demographic index (SDI) regions, utilizing data from the Global Burden of Disease (GBD) 2021 platform. An age-period-cohort (APC) model was employed to analyze the effects of age, period, and birth cohort on ADRD incidence, and a Bayesian age-period-cohort (BAPC) model was used to predict future trends. Results Globally, the age-standardized incidence rates (ASIR) remained relatively steady. However, the total number of ADRD cases witnessed a remarkable 141.25% increase, with 9,837,056 cases (95% UI: 8,620,519–11,163,700) in 2021. High SDI regions exhibited higher ASIR, whereas high-middle SDI regions showed the greatest growth, particularly among females. The net drift of ADRD incidence ranged from 0.43% per year in China to −0.68% per year in Denmark. Age effect was consistent across SDI regions, increasing exponentially with age. The 60–64 age group experienced the fastest annual incidence growth. High-middle SDI regions faced unfavorable period and cohort effects. Conclusion Although progress in ADRD globally, significant regional and sex disparities persist. Strengthened surveillance and management of adults over 60 are urgently needed. Targeted public health policies and interventions are essential to address the escalating global dementia burden.